A comparative analysis of medicine prices in Latin America - Roberto Álvarez E.; Aldo González (CEPAL Review, 2020)
This paper compares medicine prices in the six largest economies in Latin America. Using a panel-based econometric model with country fixed effects and controlling for variables related to the medicines’ characteristics, the comparison covers 19,741 units sold during the 2010–2015 period and has been carried out at the wholesale and retail levels and by type of medication (innovative, branded generic and generic). At the aggregate level and at the retail pharmacy level, the classification from least to most expensive is: Peru, Mexico, Argentina, Chile, Colombia and Brazil. In innovative medicines, Argentina and Peru have the lowest prices. In branded generic medicines, Mexico and Argentina have the lowest prices, while for pure generics, Peru and Chile appear to be the least expensive. The classification does not change substantially if ex-factory prices are compared.